×

Hello! Socratic's Terms of Service and Privacy Policy have been updated, which will be automatically effective on October 6, 2018. Please contact hello@socratic.com with any questions.

How do you convert #9=(-2x+y)^2-5y+3x# into polar form?

1 Answer
Mar 14, 2018

Answer:

#9=4r^2cos^2(theta)-4r^2sinthetacostheta+r^2sin^2(theta)-5rsintheta+3rcostheta=r(sintheta(r(sintheta−4costheta)−5)+costheta(4rcostheta+3))#

Explanation:

#x=rcostheta#
#y=rsintheta#

#9=(-2(rcostheta)+rsintheta)^2-5rsintheta+3rcostheta#

#9=4r^2cos^2(theta)-4r^2sinthetacostheta+r^2sin^2(theta)-5rsintheta+3rcostheta#

#9=r(sintheta(r(sintheta−4costheta)−5)+costheta(4rcostheta+3))#